Kebijakan dan Tantangan Pendidikan Agama Islam di Sekolah Menengah Kejuruan Non-Islam : Systematic Literature Review - Nur Azizah; Kasful Anwar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Religious diversity in Indonesia places some Muslim pupils in a minority position when attending non-Islamic schools, including vocational secondary schools run by Christian or Catholic foundations. Although regulations such as the National Education System Act and Minister of Religious Affairs Regulation No. 16 of 2010 guarantee the right of Muslim students to receive religious education in accordance with their beliefs, their implementation on the ground still presents various issues that have not been extensively examined specifically within the context of vocational secondary schools. This study aims to map the policies and challenges surrounding Islamic religious education in non-Islamic vocational secondary schools in Indonesia. The research employed a qualitative approach in the form of a systematic literature review, tracing articles from Sinta-accredited journals via Garuda and Google Scholar published within the last ten years. A synthesis of eleven journal articles revealed that policies on Islamic religious education in non-Islamic schools are underpinned by a fairly robust legal framework; however, their implementation is heavily dependent on the commitment of individual institutions. The challenges identified are multidimensional, encompassing ideological, sociological and cultural issues, as well as limitations regarding teachers and learning resources, whilst studies specifically addressing the context of vocational secondary schools remain very limited. These findings imply the need for policy evaluations that are more responsive to the unique characteristics of the vocational secondary school level, as well as further field research. to gain a deeper and more contextual understanding of this issue.